Dynamics of plasma poloidal rotation in the U-3M torsatron - Sitnikov, D.A.; Skibenko, A.I.; Tarasov, M.I.; Tarasov, I.K.; Pashnev, V.K.; Prokopenko, A.V. (Вопросы атомной науки и техники, 2011)
Results of experimental study of plasma rotation dynamics in the U-3M torsatron during transition to the improved confinement mode are presented. The rotation velocity is measured using the Doppler reflectometry methods.